2000
DOI: 10.1089/107999000312342
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IFN-gamma in Cerebrovascular Endothelial Cells from Aged Mice

Abstract: Recently, it has become clear that interferon-gamma (IFN-gamma) plays a role in the central nervous system (CNS) as well as in the immune system. However, the reason for the alteration in IFN-gamma production in the brain with aging remains unknown. In this study, we investigated the expression of IFN-gamma in the brain in terms of both mRNA and protein and compared the expression in young adult brain with that in aged mice. The cerebrum and cerebellum were collected from young adult (8-10 weeks old) and aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…3, 4). The primary sources of IFN-g in the inflamed brain are Th1 and NK cells, DCs, and macrophages, but it has also been shown that low levels of IFN-g can be produced by astrocytes, fibroblasts, cerebrovascular endothelial cells, and microglia itself in the healthy CNS (36)(37)(38). Microglia-mediated Treg induction is cell-cell contact-dependent, Ag-specific (dependent on MHC II and cognate peptide), and requires intermediate levels of CD40 and CD86 on the microglia site.…”
Section: Discussionmentioning
confidence: 99%
“…3, 4). The primary sources of IFN-g in the inflamed brain are Th1 and NK cells, DCs, and macrophages, but it has also been shown that low levels of IFN-g can be produced by astrocytes, fibroblasts, cerebrovascular endothelial cells, and microglia itself in the healthy CNS (36)(37)(38). Microglia-mediated Treg induction is cell-cell contact-dependent, Ag-specific (dependent on MHC II and cognate peptide), and requires intermediate levels of CD40 and CD86 on the microglia site.…”
Section: Discussionmentioning
confidence: 99%
“…Although T cells are the main source of IFN␥ throughout the body, these cells are relatively restricted from entering the healthy brain. However, it has been shown that low IFN␥ levels can be produced by nonimmune or non-inflammatory cells, such as astrocytes, fibroblasts, and cerebrovascular endothelial cells (Rady et al, 1995;De Simone et al, 1998;Wei et al, 2000), which comprise the resident cells of the SVZ. Our PCR analysis (data not shown) reveals that IFN␥ is present in both primary SVZ tissue and untreated neurosphere cultures.…”
Section: Discussionmentioning
confidence: 99%
“…By mimicking the inflammatory scenario in vivo, Butovsky et al (2006) have shown that cultured microglia exposed to lysophosphatidic acid and stimulated with IFN␥ support neurogenesis. Nevertheless, to date, no evidence exists to demonstrate that IFN␥ plays a role in neurogenesis in the non-inflammatory brain, although it has been shown that low levels of IFN␥ can be produced by astrocytes, fibroblasts, and cerebrovascular endothelial cells under normal conditions (Rady et al, 1995;De Simone et al, 1998;Wei et al, 2000). In the present study, we therefore investigated the effect of IFN␥ on NP activity and neurogenesis.…”
Section: Introductionmentioning
confidence: 96%
“…This cytokine is known to play a role in preventing infectious diseases and promoting a host response to tumors, but it has not been, to our knowledge, associated with aging of the epidermis (108,109). Wei and colleagues (110) have presented evidence indicating that IFN-␥ may play a role in age-associated changes that take place in mouse brain since they have found increased expression of IFN-␥ mRNA and protein during aging. Using immunofluorescence they traced the source of IFN-␥ to the cerebrovascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%